Insular Dysfunction in People at Risk for Psychotic Disorders - Gianna Sepede; Francesco Gambi; Massimo Di Giannantonio (AIMS Neuroscience, 2015)
In response to the review article written by Pavuluri and May [1] and to the original article by Tomasino et al [2] we will comment the recent neuroimaging findings of insular dysfunctions in Schizophrenia and Bipolar Disorders, focusing on people at genetic risk for developing psychotic symptoms. A disrupted insular functioning was reported in several studies, even though the results were not univocal with respect to the direction of the effect (some studies reported a reduced activation, other an augmented activation) and the lateralization of the observed alterations (left, right or bilateral). We will conclude that an altered function of the insula during both cognitive and emotional task may be a candidate vulnerability marker for psychotic disorders.